Digital memes in popular discourses a sosiological study to understand ethnic memes in algerian social media spaces - اسراء كرام (جامعة الوادي - University of Eloued, 2025)
"الملخص تسعى هذه الدراسة إلى معالجة الفجوة القائمة في الأدبيات السوسيولوجية المتعلقة بالميمات الرقمية، وذلك من خلال فحص الميمات الإثنية المتداولة داخل الفضاء الرقمي الجزائري، مع تركيز خاص على تلك التي تتناول منطقة وادي سوف. يتمثل الهدف الأساسي للدراسة في فهم الكيفية التي تسهم بها هذه الميمات في تشكيل وإعادة إنتاج التمثلات الجهوية ضمن الخطاب الشعبي على وسائل التواصل الاجتماعي، مع الكشف عن الدلالات الاجتماعية والثقافية المرتبطة بها. ترتكز الدراسة على السؤال المحوري التالي: كيف تسهم الميمات الرقمية في تشكيل وإعادة إنتاج التمثلات الجهوية لمنطقة وادي سوف في الفضاء الرقمي الجزائري؟ ويُستكمل هذا السؤال عبر مجموعة من الأسئلة الفرعية، وهي: 1. ما طبيعة الخطابات السائدة المتضمنة في هذه الميمات؟ 2. ما هي أشكال وتفسيرات تفاعلات المستخدمين؟ 3. هل تسهم هذه التفاعلات في تعزيز التماسك الاجتماعي أم تعمّق الانقسام؟ 4. إلى أي مدى تعمل الميمات على ترسيخ أو تفكيك الصور النمطية المرتبطة بمنطقة وادي سوف؟ اعتمدت الدراسة على المنهج السيميولوجي لتحليل الرموز اللغوية والبصرية، مدعومًا بإطار نظري مستند إلى نظرية التفاعلية الرمزية لفهم عملية إنتاج المعنى داخل الفضاء الرقمي. كما تم استخدام الملاحظة بالمشاركة لرصد أنماط التفاعل الاجتماعي مع هذه الميمات. وقد تكونت العينة من 15 ميمًا رقميًا تم اختيارها قصديا من صفحة ""أصيل"" على فيسبوك، مرفقة بتعليقين من المستخدمين لكل ميم. كشفت النتائج أن الميمات الرقمية لا تقتصر على كونها وسيلة للترفيه فحسب، بل تُعد أداة فاعلة في بناء المخيلة الجهوية، وتشكيل التصورات الاجتماعية، وإعادة إنتاج الصور النمطية. كما أبرزت الدراسة دور الفضاء الافتراضي كحلبة ديناميكية يتم فيها باستمرار إنتاج المعاني والهويات المحلية، لا سيما من خلال عدسة الميمات الإثنية المتعلقة بمنطقة وادي سوف. "Synopsis This study seeks to address the existing gap in sociological literature related to digital memes by examining ethnic memes circulating within the Algerian digital space, with particular focus on those addressing the Wadi Souf region. The primary objective of the study is to understand how these memes contribute to the formation and reproduction of regional representations within popular discourse on social media, while uncovering the associated social and cultural meanings. The study is guided by the central question: How do digital memes contribute to the formation and reproduction of regional representations of Wadi Souf in Algerian digital spaces? This is further explored through several sub-questions, namely: 1. What is the nature of the dominant discourses embedded in these memes? 2. What are the forms and interpretations of user interactions? 3. Do these interactions foster social cohesion or deepen division? 4. To what extent do memes reinforce or deconstruct stereotypical portrayals of WadiSouf? The study adopted a semiological methodology to analyze the linguistic and visual symbols, supported by a theoretical framework grounded in Symbolic Interactionism to understand meaning-making within the digital space. Participant observation was also employed to capture patterns of social interaction with these memes. The sample consisted of 15 digital memes sourced from the Facebook page “Asil,” each accompanied by two user comments, and was purposively selected. The findings revealed that digital memes are not limited to entertainment; rather, they serve as active tools in constructing regional imaginaries, shaping symbolic imagination, and reproducing stereotypes. The study further highlighted the role of the virtual space as a dynamic arena where meanings and local identities are continuously produced—particularly through the lens of ethnic memes related to the Wadi Souf region."
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع الاتصال.
Keywords: وسائل التواصل الاجتماعي الجزائرية; الهوية الجهوية; الفضاء الافتراضي; الخطاب الشعبي; الميم الإثني; Ethnic meme; popular discourse; virtual space; regional identity; Algerian social media